Research and development of backscatter communications technology - Yinghui YE; Rui XU; Yujia TIAN; Guangyue LU (Dianxin kexue)
As an important technology for the deployment of Internet of things (IoT), backscatter communication performs low-power passive communication and energy harvesting by applying the incident signals, which is expected to achieve energy self-sustainability of the IoT node.In order to deepen its understanding and promote the development of related fields, a review of existing research was conducted and the future development prospects were presented.Firstly, the basic principle of backscatter communication and its architecture evolution were elaborated.Secondly, in terms of different communication architectures, the existing research works were surveyed.On this basis, the hybrid active-passive mutualistic symbiotic backscatter communication was proposed, and preliminary research and simulation analysis were conducted.Finally, future research directions of the proposed communication architecture were explored based on the existing research.